Tradução e adaptação cultural para a língua portuguesa do Brasil do Sensory Perception Quotient (SPQ) - Defelippe, Raisa Coppola (2016)
Considering that approximatelly 90% of individuals with ASD show some deficit in sensory perception and the adition of atypical sensory criteria in Diagnostic and Statistical Manual of Mental Disorder, the fifith edition (DSM-5) for diagnosis of ASD, there is a need to have instruments that can access this constructs enabiling more research. Many exiting instruments are questionnaires for parents, and most of them focus on children, therefore little is known about sensory perception in adults. Given the lack of brazilian intruments to evaluate the hability of sensory processing and questionnaires that can access the real experience of who lives this reality, this study aims to translate to brazilian portuguese and culturally adapt the Sensory Perception Quotient, an instrument of self report that can access sensory reactivity in adults, evaluating five basic modalities, that can be hypo or hyper –reactive, avoiding value judgment. The purpose of this study, therefore, is to translate to brazilian portuguese and adapt culturally to the brazilian culture of the Sensory Perception Quotient, conducting a study within a scope of a non-experimental non-longitudinal descriptive research, and the following steps: translation, back-translation, revision by a specialist comittee on analysis, evaluation of he scoring and the verification of the instrument’s internal consistency. Sample was constituied of 87 participants, ages 18 to 52 years. The results obtained by the application of total questionnaire translated and adapted, already modified in 53 questions in relation to it’s original version, aloud to notice that it is understandable and shows intern consistency little under of desirable, having only the short version with desirable intern consistency. These observations indicate that the search for evidence of validy of the short version of the instrument, realized through new researches, with other applications of the translated version and adapted in this study, will make it possible to applicate in Brazil. Is recommened caution with full questionnaire in the disscution part of this study.